A comprehensive review on dry concrete: Application, raw material, preparation, mechanical, smart and durability performance. (1st September 2022) - Shao, Ruizhe; Wu, Chengqing; Li, Jun
Abstract: Dry concrete, which can be understood literally, is defined as the fresh mixture of concrete having no flowability with a very small slump value. It is a hardened mixture mixed with essentially the same raw materials (cement, aggregate and supplementary cementitious material) but lower water content as compared to conventional concrete. Performance and properties of dry concrete are closely related to the raw materials dosage, preparation technique, curing regimes and curing. At present, the applications of dry concrete products have been expanded to many engineering areas which benefit from their prominent advantages such as fast hardening, high early strength, along with low material and production cost. This paper reviews two most representative dry concrete mixtures, namely roller-compacted concrete (RCC) and dry-cast concrete (DCC), in terms of raw material, preparation method, static/dynamic mechanical behaviour, smart and durability performance, and application. Among them, the static and dynamic mechanical properties, including static strength behaviour and elastic modulus, as well as dynamic responses under seismic and impact loads, are reviewed in detail. In addition, the freeze-thaw resistance, carbonation resistance, permeability, abrasion resistance, fatigue characteristic and volume change which involved in durability investigation of both RCC and DCC are successively elaborated and analysed. Finally, some suggestions and ideas on the further researches of dry concrete are also presented. Highlights: 140 literature of journal articles, conference papers and theses are reviewed. Applications and preparation technology of dry concrete are presented. Effects of ASCMs and recycled materials on performance of dry concrete are examined. Smart dry concrete has the temperature sensing and crack self-repairing abilities. Suggestions and ideas for further study of dry concrete are elaborated.